INOVASI MODEL BIOINDUSTRI BERBASIS SAGU SPESIFIK LOKASI DI PAPUA - Petrus Alexander Beding; Niki Lewaherilla (Sepa, 2020)
The Sago Bioindustry Agriculture Model produces food raw materials in the form of flour, and sago sugar food ingredients and the use of sago waste into organic fertilizer. The results of the business analysis show that sago starch, sago sugar and fertilizer products provide benefits for increasing farmers' income and are feasible to be developed each with a business feasibility level of R / C sago flour R / C (2.44) efficiency level for venture capital 40 , 8%; sago sugar R / C value of 2.81 with an efficiency level of 22.6% and sago waste organic fertilizer value of R / C 1.3 with a level of business capital efficiency of 76%. The purpose of this research is to disseminate location-specific sago bioindustry technology innovation models in accordance with the SOP of quality sago flour production, sago-based food processing, and utilization of waste for fertilizer.